2017
DOI: 10.1186/s12917-017-1183-4
|View full text |Cite
|
Sign up to set email alerts
|

Extensive protein hydrolyzation is indispensable to prevent IgE-mediated poultry allergen recognition in dogs and cats

Abstract: BackgroundThe central premise for the commercialization of diets with hydrolyzed ingredients is that the small-sized digested peptides would be unable to crosslink allergen-specific IgE at the surface of tissue mast cells and induce their degranulation. Evidence for the validity of this concept to diagnose food allergies in dogs and cats is limited, however. Our objectives were to study the recognition of standard and variably hydrolyzed poultry extracts by sera from dogs and cats with elevated chicken-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
0
21
1
1
Order By: Relevance
“…Hydrolysis is an enzymatic proteolytic process that cleaves large proteins into small peptides, thereby reducing the allergenicity of food components . If hydrolysis is incomplete (>10 kDa), these diets retain the ability to induce AFR in dogs allergic to the original protein . Ultrahydrolysed diets (≤10 kDa) have been released on the pet food market.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis is an enzymatic proteolytic process that cleaves large proteins into small peptides, thereby reducing the allergenicity of food components . If hydrolysis is incomplete (>10 kDa), these diets retain the ability to induce AFR in dogs allergic to the original protein . Ultrahydrolysed diets (≤10 kDa) have been released on the pet food market.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive hydrolysis and absence of residual large protein fragments is key to the reliability of the diets [ 31 ]. This has been demonstrated in a recent in vitro study on the immune recognition of poultry raw materials in the sera from chicken-allergic dogs and poultry-allergic cats [ 32 ]. Classical gel electrophoresis with Coomassie blue staining was insufficiently sensitive to visualize both high molecular weight proteins as potential contaminants and the small oligopeptides and amino acids of the hydrolysate’s proteome.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated minimal to no antibody binding to the chicken hydrolysate or hydrolysed corn starch in this diet. 42,43 The diet does contain oils of different sources (coconut oil, soybean oil and fish oil). The refining process of oils for dietary consumption typically removes most protein from the oil, but trace concentrations may remain.…”
Section: Discussionmentioning
confidence: 99%